Pengaruh Online Customer Review Terhadap Keputusan Pembelian Kamar Di Kaamala Resort Ubud - Wahyuni, Ni Made Mega; Suastini, Ni Made (Program Studi Administrasi Perhotelan, 2023)
Tourism in this era of globalization is developing very rapidly which causes tourism actors to run their business by observing changes in consumers so that they can anticipate changes in consumer behavior, to then be used as material in improving marketing strategies. With the development of technology, Tourism players, especially the hotel industry, will use media distribution channels such as online travel agents as a medium for booking rooms. Data collection techniques used in this study include: documentation studies, interviews, and questionnaires. The data obtained were then analyzed using the IBM SPSS 25 (Statistical Package of Social Science). In obtaining numerical results that are in accordance with the rules, the tests are carried out on the classical assumption test, simple linear regression analysis, and the determination test. Based on the results of research that has been done, found the results that online customer reviews have a significant positive effect on purchasing decisions by 67,3 percent and 32,7 percent is influenced by other variables that not examined in this study. As an effort to improve purchasing decisions, Kaamala Resort Ubud should respond to every negative or positive review that given by consumers. and provide what the hotel promises so that expectations and reality will not be much different and consumers will become more confident to stay at Kaamala Resort Ubud.